2015
DOI: 10.1155/2016/9209825
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol Enhances the Toxic Effect of Ethanol and Acetaldehyde in Primary Mouse Hepatocytes

Abstract: Obesity and alcohol consumption are risk factors for hepatic steatosis, and both commonly coexist. Our objective was to evaluate the effect of ethanol and acetaldehyde on primary hepatocytes obtained from mice fed for two days with a high cholesterol (HC) diet. HC hepatocytes increased lipid and cholesterol content. HC diet sensitized hepatocytes to the toxic effect of ethanol and acetaldehyde. Cyp2E1 content increased with HC diet, as well as in those treated with ethanol or acetaldehyde, while the activity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 22 publications
0
15
0
2
Order By: Relevance
“…ER stress is a well‐known contributing factor that augments DNL and precipitates simple steatosis to fibrosis . Numerous evidence suggests that inclusion of fructose and cholesterol in diet instigates hepatic ER stress and NF‐κB activation . It was not surprising that γT3 is capable of suppressing hepatic ER stress against HFCS diet (Figure B), as γT3 alleviates the hepatic TG content (Figure B).…”
Section: Discussionmentioning
confidence: 97%
“…ER stress is a well‐known contributing factor that augments DNL and precipitates simple steatosis to fibrosis . Numerous evidence suggests that inclusion of fructose and cholesterol in diet instigates hepatic ER stress and NF‐κB activation . It was not surprising that γT3 is capable of suppressing hepatic ER stress against HFCS diet (Figure B), as γT3 alleviates the hepatic TG content (Figure B).…”
Section: Discussionmentioning
confidence: 97%
“…Protein concentrations were determined using a Pierce ® BCA™ Protein Assay Kit (Pierce). The following antibodies were used: SOD1 (Iuchi et al 2007), SOD2 (Iuchi et al 2007), GPx1 (Fujii et al 2002), Prx1 (Ishii et al 2005 Assay of CYP2E1 activity CYP2E1 activity was measured by the rate of oxidation of p-nitrophenol to p-nitrocatechol, as described previously (López-Islas et al 2016) with minor modifications. Briefly, a mixture containing 100 mM potassium phosphate buffer pH 7.4, 200 μM p-nitrophenol, 1 mM NADPH, was incubated with liver lysate (200 µg protein) at 37 °C for 60 min in the dark, and the reaction was terminated by adding 20 % trichloroacetic acid to the suspension.…”
Section: Western Blottingmentioning
confidence: 99%
“…Disruption of lipin‐1 signaling by lipin‐1β overexpression adenovirus vector cancelled the effect of DHA. In spite of lack of a complete understanding of the molecular mechanisms underlying alcohol‐induced hepatocyte apoptosis, mitochondrial dysfunction has been found to participate in the mechanisms . Our recent study reported that mitochondrial dysfunction induced by lipotoxicity contributes to alcohol‐induced hepatocyte injury .…”
Section: Discussionmentioning
confidence: 96%
“…Hepatocyte cell death triggered by lipotoxicity, is also called lipoapoptosis . Accumulating evidence demonstrates that oxidative stress and endoplasmic reticulum (ER) stress are the major intracellular pathways mechanistically involved in lipoapoptosis . Ethanol can also promote hepatic lipid accumulation and inflammation by activating the ER stress response.…”
Section: Introductionmentioning
confidence: 99%